1977
DOI: 10.3758/bf03335302
|View full text |Cite
|
Sign up to set email alerts
|

Methods of deconditioning persisting avoidance: Intracranial stimulation as a counterconditioner

Abstract: Rats were fixed with a chronically indwelling electrode for intracranial stimulation (lCS) of the lateral hypothalamus. Subsequent to verification that rats would barpress for ICS, they were trained in an automated one-way avoidance chamber to avoid footshock by climbing to a ledge. After 50 daily training trials on 3 consecutive days, the foots hock was terminated. One of three treatments was then programmed: (a) response prevention (retracting the ledge, forcing the rat to stay on the previously shocking gri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Yet none of these agents, as well as ethanol and morphine, which can also reduce fear and shock-motivated behavior, reduce persisting avoidance when used as adjuncts to RP. This lack of result with drugs is in marked contrast to application of positive intracranial stimulation and to prolonged RP (Baum, 1970a;Becker, Magnuson, & Reid, 1977;Gordon & Baum, 1971;Reid, 1973;Voss et aI., 1974). In the human clinic, drugs have been used successfully as adjuncts to systematic desensitization (Brady, 1966;Friedman, 1966;Kraft, 1967), but the agents used have been short-acting barbiturates.…”
Section: Discussionmentioning
confidence: 99%
“…Yet none of these agents, as well as ethanol and morphine, which can also reduce fear and shock-motivated behavior, reduce persisting avoidance when used as adjuncts to RP. This lack of result with drugs is in marked contrast to application of positive intracranial stimulation and to prolonged RP (Baum, 1970a;Becker, Magnuson, & Reid, 1977;Gordon & Baum, 1971;Reid, 1973;Voss et aI., 1974). In the human clinic, drugs have been used successfully as adjuncts to systematic desensitization (Brady, 1966;Friedman, 1966;Kraft, 1967), but the agents used have been short-acting barbiturates.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, however, the Taub et al (1977) procedure, using a single, relatively brief period of RP under the influence of a drug, provided a peculiar test of a drug's potential to modify persisting avoidance. Becker, Magnuson, and Reid (1977) did show that a counterconditioning treatment was effective as an adjunct to RP using the same basic procedure. It is possible, nevertheless, that with a longer RP period and more RP periods under the influence of drug, it can be shown that drugs are efficient adjuncts to RP.…”
mentioning
confidence: 98%